Application of CFD in Analysis of Steady and Unsteady Turbulent Flow past a Marine Propeller - Belhenniche, S. E.; Aounallah, M.; Imine, O.; Celik, F. (BEGELL HOUSE, INC, 2012)
The paper presents simulation of steady and unsteady turbulent flow in non cavitating case around the propeller of the Seiun Maru ship built in Japan. The main of this work is to reproduce the hydrodynamic characteristics of the propeller in open water [1] and in a non uniform ship wake using the commercial code ANSYS FLUENT 6.3.26 [2] based on the finite volume method by means of the RANS approach. The turbulence models k-omega standard and k-omega SST [3] were used respectively for the simulation of steady and unsteady flow. The obtained results are in a good agreement with the experiment and the error was estimated by 2% for K-Q and 5% for K-T in the steady case for a wide range of advance coefficient. The overall numerical results show that the RANS approach is applicable and can predict the hydrodynamic behavior of the water particles around the marine propeller.
Keywords: Seiun Maru propeller; Simulation; Turbulent; Steady; Unsteady; RANS; Engineering